The Influence On Service Quality On Patient Satisfaction At Rsia Bunda Aisyah - Peppy Luthfiyyah Faatin; Ari Arisman; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine and analyze the effect of service quality variables on patient satisfaction at RSIA Bunda Aisyah Tasikmalaya City. This study is a survey research with a quantitative approach, with 84 respondents who were inpatients at RSIA Bunda Aisyah Tasikmalaya City from January to June 2022. This study used a closed questionnaire with five alternative answers. Based on data processing, it is known that service quality has a positive and significant influence on customer satisfaction at RSIA Bunda Aisyah with a contribution of 78.6%.